Hubungan Antara Demokrasi dan Kesejahteraan Warga di Eropa: Analisis European Social Survey 2002-2018 - Widuri, Dina Ratih (Jurnal Ilmiah Administrasi Publik, 2021)
The welfare of citizens is one of the main goals of forming a country. Democracy is an important topic of study in public administration and is believed to be able to bring progress and prosperity to citizens. In Europe, democracy has been implemented since the 1980s. However, the welfare of citizens (in this case life satisfaction and happiness) is still a problem in Europe until recently. In addition, the effect of democracy on welfare as stated by several previous researchers still gave different results. Are citizens who live in more democratic countries more prosperous? This study uses the STATA multilevel analysis method and European Social Survey (ESS) data from 2002-2018 involving 34 countries in Europe. Broadly speaking, democracy has a positive effect on the welfare of citizens (life satisfaction and happiness) in Europe. People living in Western Europe have the most prosperous life compared to people living in other parts of Europe, especially Eastern Europe. It was also found that the number of women in parliament greatly influences the welfare of citizens in Europe.